What is needed to promote physical activity? - Vivien Hohberg; Jan-Niklas Kreppke; Robyn Cody; Regina Guthold; Catherine Woods; Ralf Brand; Genevieve Dunton; Alexander Rothman; Sascha Ketelhut; Claudio Nigg (Bern Open Publishing, 2022)
Despite the health-related benefits and published evidence-based physical activity (PA) guidelines, global PA levels have been stagnating since the 2000s, with around 80% of adolescents and 28% of adults not achieving the recommendations. As a result, a pandemic of physical inactivity is occurring, with far-reaching health consequences along with a substantial economic burden. This has led to the development of the Global Action Plan on Physical Activity 2018-2030 (GAPPA). GAPPA includes recommendations and 20 related evidence-based policy actions, which are adaptable across country contexts. The Irish PA Research Collaboration implemented strategies from the GAPPA at a national level and thus, conducted a systems map to identify gaps and strengths in PA policy. Using this approach, the Move for Life intervention was successfully developed, implemented, and evaluated. In line with a whole system approach, a better understanding of the individual is also required in the course of successfully promoting and maintaining PA. Affective-Reflective Theory of physical inactivity and exercise highlights the importance of learnt affective responses to exercise-related stimuli, and suggests that both automatic and controlled processes contribute to the adoption and maintenance of a physically active lifestyle. A method to shed light on motivational processes and people's everyday behavior is longitudinal micro-temporal data. During the challenging situations such as the COVID-19, longitudinal micro-temporal data collected through mobile and wearable devices can capture processes and conditions that underlie flexible shifting between the automatic and controlled processes needed to maintain behavior. In summary, this paper compiles key concepts for PA promotion and maintenance, from which future directions follow: Gathering more extensive PA and sedentary behavior data; applying a whole system approach; considering new perspectives with a dual mode approach; avoiding unpleasant feelings during PA or exercise; conceiving interventions that promote flexibility; and capitalizing on technology to integrate and achieve these future directions.